Comparison of Retinal Microvessel Blood Flow Velocities Acquired with Two Different Fields of View - Jin Zhou; Min Li; Wan Chen; Ye Yang; Liang Hu; Liang Wang; Hong Jiang; Jianhua Wang (Journal of Ophthalmology)
To compare the different retinal blood flow velocities (BFVs) acquired with different fields of view (FOVs) using the retinal function imager (RFI), twenty eyes of twenty healthy subjects were enrolled in the study. Retinal microvessel BFV in the macula was acquired with both a wide FOV (35 degrees, 7.3 × 7.3 mm2) and a commonly used small FOV (20 degrees, 4.3 × 4.3 mm2). The 35-degree FOV was trimmed to be equivalent to the 20-degree FOV to compare the BFVs of the similar FOVs using different settings. With the 35-degree FOV, both retinal arteriolar and venular BFVs were significantly greater than the 20-degree FOV (P<0.001). When the 20-degree FOV was compared to the trimmed equivalent 20-degree FOV acquired using the 35-degree FOV, significant BFV differences were found in both the arterioles (P=0.029) and venules (P<0.001). This is the first study to compare retinal blood flow velocities acquired with different FOVs using RFI. The conversion factor from 35 degrees to 20 degrees is 0.95 for arteriolar BFV and 0.92 for venular BFV, which may be used for comparing BFVs acquired with different FOVs.